A comparative study of laparoscopic cholecystectomy with and without abdominal drain - Soubhik Sarkar; Shib Shankar Kuiri; Yadhu Rajan; Kanchan Kundu (Asian Journal of Medical Sciences, 2023)
Background: Laparoscopic cholecystectomy (LC) has been considered the Gold-standard for the management of benign gallbladder disease. With increasing surgeon experience and advancement of instrumentations and equipment, LC is approaching continuously toward a more safe and less invasive technique. There is a consensus that drainage should not be considered mandatory or standard after elective LC. Aims and Objectives: The aims of this study were to assess the effectiveness of the LC without abdominal drain over sub hepatic drainage and to compare the post-operative outcome between two groups. Materials and Methods: A descriptive observational comparison study has been carried out in the department of General Surgery BSMCH, from September 1, to December 1, in 130 patients undergoing elective LC. Patients have been divided into two groups: Comparison group and study group after proper matching. Data have been collected via interview, clinical examination, and scrutinizing relevant medical records. Each patient has been followed up after operation. Data have been summarized for estimating various parameters such as mean duration of surgery and hospital stay between the groups and proportion of patient complaining of pain 24 h after surgery. Results: The mean duration of surgery in drainage group is 108 min which is significantly more than the non-drainage group 88 min. In this present study, the patients with abdominal drain are showing more incidence of post-operative nausea and vomiting (PONV) 21.53% compared to no-drain group 6.15%. In this study, 35.38% of patients with subhepatic drain developed pain after surgery, whereas only 12.3% of the patients with no drain experienced the same. Overall six patients from the drain group still had significant subhepatic collection and eight patients with no drain have the same. The mean duration of stay in hospital of the drain group is 4.06 days, whereas, in no-drain group, it is 2.26. Conclusion: An uncomplicated gallstone disease can be treated by LC without need for drain with reasonable safety by an experienced surgeon. Hence, no use of drain scores over use of drain in terms of PONV, post-operative pain, and therefore, there is less use of analgesics and also short duration of hospital stay. When a dry operative field is achieved during LC the drain insertion may be avoided.